A composite electrode and its preparation method and its application in alkali metal ion battery

By using the preparation method of composite electrode sheets in alkali metal ion batteries, using the heat treatment and sintering technology of soft carbon materials to form composite electrode sheets, solving the disadvantages of existing negative electrode materials in terms of magnification and low-temperature performance, and achieving efficient circulation and safety improvement of the battery.

CN119742320APending Publication Date: 2025-04-01惠州赣锋锂电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962550.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The negative electrode materials of existing alkali metal ion batteries have great disadvantages in terms of rate performance and low temperature performance, especially the silicon-carbon materials expand severely during the cycle, which affects the cycle life and safety of the battery.

Method used

By using the preparation method of the composite electrode sheet, a second active material is obtained by heat treatment and sintering of the soft carbon material, and is laminated with the first active material to form a composite electrode sheet. This method reduces the overall expansion of the negative electrode by acting as a dielectric of the soft carbon layer, and improves cycle life and kinetic performance.

Benefits of technology

The excellent rate performance and low-temperature charging and discharging performance of composite electrode sheets in alkali metal ion batteries are achieved, which extends the cycle life of the battery and reduces the overall manufacturing cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742320A_ABST
    Figure CN119742320A_ABST
Patent Text Reader

Abstract

The present invention provides a composite pole piece and a preparation method thereof and an application in an alkali metal ion battery, belonging to the technical field of alkali metal ion batteries. The present invention sequentially heat treats and sinters a soft carbon material, uses the sintered product as a second active material, loads it on a pole piece containing a first active material layer, and obtains a composite pole piece by rolling. Among them, the functional groups in the form of ether, epoxy and hydroxyl in the sintered soft carbon are conducive to improving the wettability of the electrolyte, providing more active sites for lithium ion deposition, and increasing the proportion of negative electrode pseudocapacitance. At the same time, a small amount of highly regular graphite microcrystals is retained in the structure, and the conductivity is good, thereby improving the dynamic performance and low temperature performance; the present invention coats the second active material layer (soft carbon layer) on the first active material layer, which is conducive to buffering the expansion stress caused by ion embedding into the material during the cycle, reducing the overall expansion of the negative electrode, and improving the cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alkali metal ion batteries, and in particular to a composite pole piece and a preparation method thereof, and application thereof in alkali metal ion batteries. Background Art

[0002] As secondary batteries are increasingly used in consumer electronics and power batteries, the requirements for alkali metal ion batteries' energy density, rate performance, low temperature performance, and long cycle life are becoming higher and higher. However, the above performance is greatly affected by the negative electrode material. In order to maximize battery performance and cycle life, the negative electrode material needs to meet the requirements of high conductivity, ionic conductivity, and low volume expansion.

[0003] Currently, for lithium-ion batteries, graphite and silicon-carbon have been widely developed. Although they have been commercially used so far, the kinetics and cycle volume expansion of graphite negative electrodes have not been greatly improved. Silicon-carbon materials have very high capacity, which is helpful for improving the overall energy density of the battery. However, silicon materials expand severely during the cycle process. Excessive expansion will cause particle pulverization, thus affecting the cycle life and safety of the battery. At the same time, silicon-carbon materials are difficult to withstand ion insertion and extraction at high rates, showing worse kinetic performance. In low-temperature environments, ion transmission is slow, and the longer transmission path of silicon-carbon materials also leads to incomplete deposition of lithium ions, showing poor electrochemical performance.

[0004] Therefore, existing negative electrode materials such as silicon carbon and graphite have poor kinetics and have great disadvantages in rate performance and low-temperature charge and discharge performance. Summary of the invention

[0005] The object of the present invention is to provide a composite pole piece and a preparation method thereof and application in an alkali metal ion battery, wherein the composite pole piece has excellent rate performance and low-temperature charge and discharge performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a composite pole piece, comprising the following steps:

[0008] The first active material is mixed with the first auxiliary material, the obtained slurry is coated on the current collector, and after the first vacuum drying, the slurry is rolled to obtain an intermediate negative electrode sheet;

[0009] The soft carbon material is granulated, and the obtained precursor particles are heat-treated to obtain an intermediate product;

[0010] After sintering the intermediate product, a second active material is obtained;

[0011] The second active material is mixed with the second auxiliary material, and the obtained slurry is applied to the intermediate negative electrode sheet, and after a second vacuum drying, the slurry is rolled to obtain a composite electrode sheet;

[0012] The first active material includes graphite, silicon carbon, hard carbon or silicon oxygen material.

[0013] Preferably, the first auxiliary material includes a first conductive agent and a first binder; the mass ratio of the first active material to the first conductive agent and the first binder is 95-98.2:0-1.5:1-5.

[0014] Preferably, the surface density of the first active material on the current collector is 5 to 12 mg / cm 2 The temperature of the first vacuum drying is 60 to 120°C and the time is 2 to 24 hours.

[0015] Preferably, the soft carbon material includes coal tar, petroleum tar or anthracite.

[0016] Preferably, the temperature of the heat treatment is 100 to 450° C., the holding time is 1 to 10 hours, and the heating rate to the heat treatment temperature is 1 to 10° C. / min.

[0017] Preferably, the sintering temperature is 600-1400° C., and the holding time is 1-10 h; the heating rate to the sintering temperature is 1-10° C. / min.

[0018] Preferably, the second auxiliary material includes a second conductive agent and a second binder; the mass ratio of the second active material to the second conductive agent and the second binder is 95-98.2:0-1.5:1-5; the mass ratio of the first active material to the second active material is 10-19:1-10.

[0019] Preferably, the surface density of the second active material on the intermediate negative electrode sheet is 5 to 10 mg / cm 2 The temperature of the second vacuum drying is 60 to 120°C and the time is 2 to 24 hours.

[0020] The present invention provides a composite pole piece prepared by the preparation method described in the above technical solution, comprising a current collector layer, a first active material layer and a second active material layer stacked in sequence.

[0021] The present invention provides the application of the composite pole piece described in the above technical solution in an alkali metal ion battery.

[0022] The present invention provides a method for preparing a composite pole piece, wherein a soft carbon material is subjected to heat treatment and sintering in sequence, and the sintered product is used as a second active material, loaded on a pole piece containing a first active material layer, and rolled to obtain a composite pole piece. Among them, the functional groups in the form of ether, epoxy and hydroxyl in the sintered soft carbon are conducive to improving the wettability of the electrolyte, providing more active sites for lithium ion deposition, and increasing the proportion of negative electrode pseudocapacitance. At the same time, a small amount of highly regular graphite microcrystals is retained in the structure, and the conductivity is good, thereby improving the dynamic performance and low temperature performance.

[0023] Since the adsorption capacity of soft carbon accounts for a large proportion during the charge and discharge process, the interlayer spacing is large, and the structure is relatively stable, it has a small expansion during the cycle process (especially under high-rate charge and discharge conditions); the present invention coats the second active material layer (soft carbon layer) on the first active material layer, which is beneficial to buffer the expansion stress caused by ion embedding into the material during the cycle, reduce the overall expansion of the negative electrode, increase the cycle life, and improve the overall kinetics and low-temperature performance.

[0024] The present invention uses soft carbon as raw material, has the advantages of wide raw material sources and simple processing technology, thereby reducing the overall manufacturing cost.

[0025] Although the defects and functional groups on the surface of soft carbon can improve the kinetic performance, it consumes more electrolyte than other negative electrode materials, which may lead to a decrease in battery cycle performance. The present invention further controls the ratio of the first active material layer to the second active material layer to avoid excessive soft carbon from reducing the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The flowchart of the preparation method of the composite pole piece of the present invention;

[0027] Figure 2 It is a schematic diagram of the structure of the composite pole piece of the present invention;

[0028] Figure 3 This is a SEM image of the graphite pole piece prepared in Comparative Example 1;

[0029] Figure 4 This is the SEM image of the soft carbon particles in Example 1. DETAILED DESCRIPTION

[0030] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0031] like Figure 1 As shown, the present invention provides a method for preparing a composite pole piece, comprising the following steps:

[0032] The first active material is mixed with the first auxiliary material, the obtained slurry is coated on the current collector, and after the first vacuum drying, the slurry is rolled to obtain an intermediate negative electrode sheet;

[0033] The soft carbon material is granulated, and the obtained precursor particles are heat-treated to obtain an intermediate product;

[0034] After sintering the intermediate product, a second active material is obtained;

[0035] The second active material is mixed with the second auxiliary material, and the obtained slurry is applied to the intermediate negative electrode sheet, and after a second vacuum drying, the slurry is rolled to obtain a composite electrode sheet;

[0036] The first active material includes graphite, silicon carbon, hard carbon or silicon oxygen material.

[0037] The present invention mixes the first active material with the first auxiliary material, and the obtained slurry is coated on the current collector. After the first vacuum drying, the slurry is rolled to obtain the intermediate negative electrode sheet.

[0038] In the present invention, the first active material includes graphite, silicon carbon, hard carbon or silicon oxygen material. The present invention has no special limitation on the source or specific structure of the first active material, and any corresponding material obtained in a manner well known in the art can be used.

[0039] In the present invention, the first auxiliary material preferably includes a first conductive agent and a first binder; the first conductive agent is preferably carbon nanotubes, Ketjen black, conductive carbon black or superP, and the first binder is preferably SBR or PAA (polyacrylic acid). The mass ratio of the first active material to the first conductive agent and the first binder is preferably 95-98.2:0-1.5:1-5, and more preferably 97:0.5:2.5.

[0040] The present invention has no special limitation on the current collector, and any current collector known in the art can be used. In an embodiment of the present invention, the current collector is specifically copper foil.

[0041] In the present invention, the surface density of the first active material on the current collector is preferably 5 to 12 mg / cm 2 , more preferably 6 to 10 mg / cm 2 , more preferably 8.9 mg / cm 2 .

[0042] In the present invention, the temperature of the first vacuum drying is preferably 60 to 120° C., more preferably 90 to 100° C., and the time is preferably 2 to 24 hours, more preferably 12 to 18 hours.

[0043] After the first vacuum drying is completed, the temperature of the present invention is naturally lowered to room temperature and roller pressed.

[0044] The present invention has no special limitation on the coating and rolling, and the intermediate negative electrode sheet can be obtained by coating and rolling according to methods and conditions well known in the art.

[0045] The present invention granulates the soft carbon material, and heat-treats the obtained precursor particles to obtain an intermediate product.

[0046] In the present invention, the soft carbon material preferably includes coal tar pitch, petroleum tar pitch or anthracite. The present invention has no particular limitation on the source of the soft carbon material, and any commercially available product known in the art or obtained in a manner known in the art may be used.

[0047] The present invention preferably performs crushing, screening and granulation treatments on the soft carbon material in sequence to obtain precursor particles; the present invention has no special limitation on the conditions of the crushing, screening and granulation treatments, and can be carried out according to the processes well known in the art; the present invention has no special limitation on the particle size of the precursor particles, and can be adjusted according to actual needs; in the embodiment of the present invention, it is specifically 5 mm.

[0048] In the present invention, the temperature of the heat treatment is preferably 100-450°C, more preferably 200-350°C, further preferably 250-300°C, the holding time is preferably 1-10h, more preferably 2-5h, and the atmosphere is air; the heating rate to the temperature of the heat treatment is 1-10°C / min, more preferably 5°C / min.

[0049] The present invention uses heat treatment to make the soft carbon material more fully combine with oxygen, thereby realizing more oxygen functional groups and surface defects, providing more active sites for subsequent lithium ion deposition. However, if the heat treatment temperature is too high, carbon will combine with oxygen to form carbon monoxide and carbon dioxide, which will volatilize. Therefore, low-temperature heat treatment needs to be controlled.

[0050] After obtaining the intermediate product, the present invention sintered the intermediate product to obtain the second active material.

[0051] In the present invention, the sintering temperature is preferably 600-1400°C, more preferably 700-1000°C, further preferably 850-900°C, and the holding time is preferably 1-10h, more preferably 2-5h; the heating rate to the sintering temperature is preferably 1-10°C / min, more preferably 5°C / min; the sintering is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen, argon, a nitrogen-argon mixture or ammonia; the present invention has no special limitation on the volume ratio of nitrogen and argon in the nitrogen-argon mixture, which can be adjusted according to actual needs.

[0052] In the high temperature environment of the sintering, the carbon material structure develops into an orderly arrangement, which is more conducive to the embedding of lithium ions. At the same time, sintering in an inert atmosphere is accompanied by a dehydrogenation reaction, and at the same time, it is accompanied by the volatilization of substances such as water, organic compounds, carbohydrates, and lipids, which improves the lithium storage effect while reducing the risk of subsequent side reactions between such substances and the electrolyte.

[0053] After the sintering is completed, the present invention preferably performs jet milling and sieving treatments on the obtained product in sequence to obtain the second active material; the sieving product D 50 The particle size is preferably 0.1 to 5 μm, more preferably 2 μm. The present invention has no particular limitation on the conditions of the jet mill pulverization and screening treatment, and the desired particle size can be achieved by following the process known in the art.

[0054] After obtaining the second active material, the present invention mixes the second active material with the second auxiliary material, applies the obtained slurry to the intermediate negative electrode sheet, and after a second vacuum drying, rolls to obtain a composite electrode sheet.

[0055] In the present invention, the second auxiliary material preferably includes a second conductive agent and a second binder; the second conductive agent is preferably carbon nanotubes, Ketjen black, conductive carbon black or superP, and the second binder is preferably SBR or PAA (polyacrylic acid); the mass ratio of the second active material to the second conductive agent and the second binder is preferably 95-98.2:0-1.5:1-5, more preferably 97:0.5:2.5.

[0056] In the present invention, the mass ratio of the first active material to the second active material is preferably 10-19:1-10, and more preferably 10-18:2-10.

[0057] In the present invention, the surface density of the second active material on the intermediate negative electrode sheet is preferably 5 to 10 mg / cm 2 , more preferably 6 to 8 mg / cm 2 .

[0058] In the present invention, the temperature of the second vacuum drying is preferably 60 to 120° C., more preferably 90 to 100° C., and the time is preferably 2 to 24 hours, more preferably 12 to 18 hours.

[0059] The present invention has no particular limitation on the coating and rolling, and the coating and rolling can be carried out according to methods well known in the art.

[0060] like Figure 2 As shown, the present invention provides a composite electrode sheet prepared by the preparation method described in the above technical solution, comprising a current collector layer, a first active material layer and a second active material layer stacked in sequence.

[0061] In the present invention, the first active material layer is a conventional lithium battery negative electrode material (graphite, silicon carbon). Soft carbon is difficult to be used alone as a mature lithium battery negative electrode material due to microstructural problems, but its surface defects and functional groups can provide active sites for lithium ion deposition and shorten the deposition path. Conventional graphite or silicon carbon negative electrode material surfaces contain very few similar active sites. Therefore, the present invention deposits a soft carbon layer (second active material layer) on the surface of the first active material layer to improve the overall kinetics and low-temperature performance.

[0062] The present invention provides the application of the composite electrode sheet of the above technical solution in an alkali metal ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art. The alkali metal ion battery of the present invention preferably includes lithium, sodium, and potassium ion batteries.

[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] (1) The first active material (graphite, D 50 The active material (SWCNT) was used as the active material, and the conductive agent (SWCNT) and the binder (SBR) were mixed in a ratio of 97:0.5:2.5 to prepare a slurry. The prepared slurry was evenly coated on the copper foil. The surface density of the first active material on the copper foil was 8.9 mg / cm 2 The obtained material was placed in a vacuum drying oven at 90°C for 12 hours, and after natural cooling, the electrode was taken out and rolled to obtain an intermediate negative electrode;

[0066] (2) crushing and screening the coal tar pitch, and granulating the obtained coarse coal tar pitch particles to obtain precursor particles (i.e., soft carbon particles) with an average particle size of 5 mm;

[0067] (3) placing the precursor particles into a muffle furnace and heating them to 250° C. at a heating rate of 5° C. / min, performing a pre-oxidation heat treatment in an air atmosphere, and keeping the temperature for 2 h; taking them out after they are cooled naturally to obtain an intermediate product;

[0068] (4) The intermediate product after pre-oxidation was sent to a tubular furnace and heated to 850°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 2 h for carbonization treatment. After the temperature dropped naturally, the sample was taken out, pulverized by jet milling, sieved, and D was controlled. 50 The particle size is 2 μm, and a coal tar pitch soft carbon material is obtained as the second active material;

[0069] (5) The obtained second active material is used as an active material, and mixed in a mass ratio of active material: conductive agent (SWCNT): binder (SBR) = 97:0.5:2.5 to prepare a slurry, and the obtained slurry is evenly coated on the intermediate negative electrode sheet prepared in step (1), and the mass ratio of the first active material to the second active material is controlled to be 18:2, and the surface density of the second active material on the electrode sheet is 8 mg / cm 2 , and put it into a vacuum drying oven at 90°C for vacuum drying for 12 hours. After natural cooling, take out the electrode sheet and roll press it to obtain a composite negative electrode sheet.

[0070] Example 2

[0071] The only difference from Example 1 is that in step (5), the mass ratio of the first active material to the second active material is controlled to be 10:10.

[0072] Comparative Example 1

[0073] Graphite was mixed in a mass ratio of active material: conductive agent: binder = 97:0.5:2.5 to prepare a slurry, and the obtained slurry was evenly coated on the copper foil, and the surface density of the graphite on the copper foil was controlled to be 8.9 mg / cm 2 , and put it into a vacuum drying oven at 90℃ for 12h. After natural cooling, take out the electrode sheet and roll it twice to obtain a graphite negative electrode sheet.

[0074] Test Case

[0075] 1) Figure 3 This is the SEM image of the graphite negative electrode sheet of Comparative Example 1. Figure 4 is the SEM image of the soft carbon particles in Example 1. Figure 3 It can be seen that the graphite negative electrode has a relatively complete layered structure and high crystallinity, which is conducive to the embedding of lithium ions. However, at high rates, lithium ions cannot be quickly embedded in this layered structure, so it exhibits poor rate performance. Figure 4 Medium-soft carbon particles exhibit relatively disordered characteristics and have a relatively open crystal structure. Combined with the micropores and defects on the surface, they will have a significant improvement in dynamics.

[0076] The negative electrode sheets prepared in Examples 1 to 2 and Comparative Example 1 were respectively prepared with the matching lithium cobalt oxide positive electrode sheets to form soft-packed cells. The cell preparation process: the prepared positive and negative electrode sheets were sheeted, and then wound with PP separators to form bare cells, followed by conventional packaging, baking, and injection (electrolyte composition: 1 mol / L LiPF 6 , EC:DEC:EMC=1:1:1, volume ratio), formation, secondary sealing, capacity division, and obtaining a finished lithium-ion battery cell.

[0077] Test conditions:

[0078] Low temperature performance test: The finished battery cell was placed in a -10℃ constant temperature box for 2 hours, then discharged at a constant current of 0.2C to 3.0V, placed for 30 minutes, charged at a constant current and constant voltage of 0.5C to 4.5V, placed for 30 minutes, and finally discharged at a constant current of 0.2C to 3.0V to obtain the final discharge capacity.

[0079] Rate performance: The battery cell is discharged at 0.2C at room temperature, and then charged to 4.5V at 0.2C constant current and constant voltage, and the corresponding charging capacity at 0.2C rate is obtained. The same battery cell is discharged to 3.0V, and then charged to 4.5V at 3C constant current and constant voltage, and the corresponding charging capacity at 3C is obtained; the rate performance is the ratio of the corresponding capacities at the two rates.

[0080] The performance test results are shown in Table 1.

[0081] Table 1 Comparison of some performances of soft-pack batteries made from the composite negative electrode sheets in Example 1 and Example 2 and the graphite negative electrode in Comparative Example 1

[0082] Example 1 Example 2 Comparative Example 1 -10℃ capacity (mAh) 2713.6 2495.3 2608.4 Rate performance (3C / 0.2C) 96.33% 98.41% 94.71% Cycle expansion rate after 100 cycles at 25℃ 2.61% 2.46% 3.17%

[0083] As can be seen from Table 1, the negative electrode after the composite soft carbon layer has a higher capacity than conventional negative electrode materials due to the change in kinetics in a low temperature environment of -10°C, and the rate performance is also significantly improved. At the same time, due to the inhibitory effect of the soft carbon layer and its own small expansion rate, the battery cell prepared by the composite negative electrode has a smaller expansion effect. For Example 2, due to the interlayer spacing and structure of the soft carbon, its theoretical capacity and lithium storage capacity at low rates are not as good as graphite. Therefore, the introduction of too much soft carbon will lead to the loss of its lithium storage capacity. In this regard, the amount of soft carbon should be controlled, but compared with Comparative Example 1, it also has a great improvement in rate performance and cycle expansion.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite pole piece, characterized in that: The following steps are involved: The first active material is mixed with the first auxiliary material, the obtained slurry is coated on the current collector, and after the first vacuum drying, the slurry is rolled to obtain an intermediate negative electrode sheet; The soft carbon material is granulated, and the obtained precursor particles are heat-treated to obtain an intermediate product; After sintering the intermediate product, a second active material is obtained; The second active material is mixed with the second auxiliary material, and the obtained slurry is applied to the intermediate negative electrode sheet, and after a second vacuum drying, the slurry is rolled to obtain a composite electrode sheet; The first active material includes graphite, silicon carbon, hard carbon or silicon oxygen material.

2. The preparation method according to claim 1, characterized in that: The first auxiliary material includes a first conductive agent and a first binder; the mass ratio of the first active material to the first conductive agent and the first binder is 95-98.2:0-1.5:1-5.

3. The preparation method according to claim 1, characterized in that: The surface density of the first active material on the current collector is 5 to 12 mg / cm 2 The first vacuum drying temperature is 60 to 120°C and the time is 2 to 24 hours.

4. The preparation method according to claim 1, characterized in that: The soft carbon material includes coal tar pitch, petroleum tar pitch or anthracite.

5. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 100-450° C., the heat preservation time is 1-10 hours, and the heating rate to the heat treatment temperature is 1-10° C. / min.

6. The preparation method according to claim 1, characterized in that: The sintering temperature is 600-1400° C., and the heat preservation time is 1-10 hours; the heating rate to the sintering temperature is 1-10° C. / min.

7. The preparation method according to claim 1, characterized in that: The second auxiliary material includes a second conductive agent and a second binder; the mass ratio of the second active material to the second conductive agent and the second binder is 95-98.2:0-1.5:1-5; the mass ratio of the first active material to the second active material is 10-19:1-10.

8. The preparation method according to claim 1, characterized in that: The surface density of the second active material on the intermediate negative electrode sheet is 5 to 10 mg / cm 2 The temperature of the second vacuum drying is 60 to 120°C and the time is 2 to 24 hours. 9 . The composite electrode sheet prepared by the preparation method according to claim 1 , comprising a current collector layer, a first active material layer and a second active material layer stacked in sequence.

10. Use of the composite electrode according to claim 9 in an alkali metal ion battery.